A study to detect early lung function deterioration using forced oscillation technique in smokers - Kirtish Bhutda; Sanjay Kumar Bharty; Avinash Jain; Vikas Patel; Brij Bihari Patel; Brahma Prakash (Asian Journal of Medical Sciences, 2023)
Background: Scientists unequivocally evidenced that tobacco consumers suffer from three Ds: disease, disability, and death. The forced oscillation technique (FOT) is a non-invasive method with which to measure respiratory mechanics. Aims and Objectives: This study was done to evaluate the ability of FOT to detect early smoking-induced respiratory function deterioration and to compare the performance of FOT with spirometry in healthy smokers. Materials and Methods: A cross-sectional study was conducted at a medical college between January 1st, 2021, and June 31st, 2022, with a sample size of 30. Study participants included healthy smokers and non-smokers. Spirometry and FOT were taken into consideration as a diagnostic modality. Data analysis was done through statistical software with a confidence interval of 95% and P<0.5. Results: In a total of 30 sample size (15 cases and 15 control), smokers presented with an average age of 26.13±5.55 years, with smoking index (SI) ranging from 5 to 80, none of the spirometry parameters were statistically significant between smokers and non-smokers, however, the FOT parameter, resistance at 6-hertz frequency R6, in smokers is 5.36±3.36 and is statistically different from non-smokers (P=0.02). Similarly, the percent predicted value of R6 also was statistically different in smokers (P=0.01). The R6 parameter correlated with forced expiratory flow 25–75 parameter of spirometry (r=0.567, P=0.027) in smokers. Conclusion: FOT is a good diagnostic modality in detecting early airway changes in smokers. The FOT along with spirometry increases the chances of diagnosing early airway changes in even initial smokers having a low SI.